Ochrona zwyczaju Maorysów w prawie nowozelandzkim - Siekiera, Joanna (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
The article is an attempt to present the contemporary forms of legal protection over the Maori norms, that is the customary law. As the New Zealand legal system appears not well analysed or researched on the Polish nor European ground, an author wishes to bring closer such terms as: Maori custom, indigenous rights, tikanga Maori, Treaty of Waitangi, as well as the following Waitangi Tribunal. It has to be underlined that New Zealand, also called Aotearoa in the 2nd official Maori language, possesses a mixed legal system, where the Maori norms are equal and binding. Very often, though, those values prevail over other parliamentary acts due to being ranked as the highest, constitutional source of law. Social transformation of the New Zealand society has ultimately altered perception of the Maori rights, including the historical claims dated back to the 19th century. As a consequence of the Waitangi Tribunal establishment, the Maori minority is finally able to execute its privileges. However it applies also for the future, as the Treaty of Waitangi found the continuous partnership between Maori and the Crown. Therefore, one can see the on-going role of this court in protection along with implementation of any rights of the indigenous people
Keywords: Nowa Zelandia; Maorysi; zwyczaj maoryski; maoryskie prawo; prawo nowozelandzkie; autochtoni; Waitangi